1999
DOI: 10.1021/jp992252w
|View full text |Cite
|
Sign up to set email alerts
|

Acid−Base Chemistry on Crystalline Ice:  HCl + NH3

Abstract: The chemical interaction of (i) HCl, (ii) NH 3 , and (iii) HCl + NH 3 with crystalline ice has been examined as a function of temperature (T ) 80-150 K) utilizing FTIR spectroscopy. The infrared spectra reveal the formation of ionic hydrates for HCl and molecular hydrates for NH 3 . The acid-base reaction leads to the formation of the ammonium ion, NH 4 + . While it is produced to a limited extent between 80 and 140 K, NH 4 + is a dominant species above 140 K. All species appear as lower amorphous hydrates for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 44 publications
5
49
0
Order By: Relevance
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…To date, TP-TOF-SIMS has revealed that both HCl and NH 3 molecules adsorbed on pure ASW films are hydrated considerably up to 140 K [22][23][24], which is consistent with the conclusions drawn using different approaches [3][4][5][6]8,9,13,14]. However, very little is known about intermolecular interactions at the surface of acidic and basic water-ice films including hydrated HCl or NH 3 molecules, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Molina et al [1] proposed that the reaction rate between HCl and ClNO 2 is enhanced considerably by the existence of ice particles, but detailed reaction pathways for the ionization and solvation of HCl adsorbed on a water-ice surface are not yet fully understood. So far, a number of groups have been extensively tackling these fascinating topics by infrared spectroscopy (IR) [3][4][5][6][7][8][9], reactive Cs + ion scattering (RIS) [10,11], near edge X-ray absorption fine structure (NEXAFS) [12], and temperature-programmed desorption (TPD) [8,9,13,14] analyses, and computer simulations [3,5,[15][16][17][18][19][20][21]. Recently, arguments tend to converge on the conclusion that both the ionization and solvation of HCl molecules occur as proposed by Devlin and coworkers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…been investigated only scarcely at ice surfaces [12][13][14] compared to its intense study in liquid water. [15] Herein, we study the proton-transfer reactions from the hydronium ion to a series of amine molecules [NH 3 , CH 3 NH 2 , and (CH 3 ) 2 NH] at ice surfaces.…”
mentioning
confidence: 99%
“…The features at approximately 1470 and 1100 cm À1 in Figure 3f are the n 4 (asymmetric deformation) band of NH 4 + and the n 2 (umbrella) band of NH 3 on the H 2 O monolayer, respectively. [32][33][34][35][36] On the D 2 O monolayer, NH 3 D + is the most abundant ammonium isotopologue at low temperature, as seen from the LES results in Figure 2b. Theoretical calculations predict that ammonium isotopologues (NH x D 4Àx + ) have vibrational frequencies in the range 1400-1500 cm…”
Section: Spectroscopic Evidence Of Acidic Watermentioning
confidence: 74%